New Attorney Swearing-in Ceremony at Exhibit Hall - Watkins, Howard::::::::: (1980)
Judges Dean Price and Eckhart Thompson, Justices Ken Andreen, George Zenovich, George Brown, George Hopper, Pauline Hanson and other Judge